Guideline for Innovation Management Design of Home Bathroom Environment to Help Reduce Accident Risk among Elderly - Junprateep, Chartchay; Seviset, Somchai; Eakwutvongsa, Songwut (Mediterranean Journal of Social Sciences, 2020)
The present research was aimed to investigate the space and accident risk factors of elderly in home bathroom, risk problems, and the current functional limitations for elderly. The study investigated spaces of bathrooms in 30 homes currently living by elderly by conducting an assessment of proper bathroom environmental features, and interviews with the elderly at home. Results of assessment of bathroom spaces of all homes under the study categorized into 5 aspects of importance suggested a low level of propriety ( = 2.22 , S.D.=0.85). For sub-aspects of importance, suitable size and proportion were at a low level ( = 2.18 , S.D.=0.73), and the design materials were at a lowest level ( = 1.26 , S.D.=0.41). In conclusion, all of the studied spaces were found with inappropriate environment to accommodate the use by elderly. The researcher recognized the problems, roles, and importance of involved individuals and thus proposed guidelines for the design of home bathroom under the universal design concept so as to guide good standards as a key factor for taking improvement action for accident prevention and preparation of sound environment for elderly.